Morphometric and allometric rules of polyp's landscape in regular and chimeric coral colonies of the branching species Stylophora pistillata. Issue 5 (31st December 2020) - Guerrini, Gabriele; Shefy, Dor; Shashar, Nadav; Shafir, Shai; Rinkevich, Baruch
Abstract: Background: Most studies on architectural rules in corals have focused on the branch and the colony level, unveiling a variety of allometric rules. Working on the branching coral Stylophora pistillata, here we further extend the astogenic directives of this species at the polyp level, to reveal allometric and morphometric rules dictating polyps' arrangement. Results: We identified a basic morphometric landscape as a six‐polyp circlet developed around a founder polyp, with established distances between polyps (six equilateral triangles), reflecting a strong genetic‐based background vs high plasticity on the population level. Testing these rules in regular and chimeric S. pistillata colonies, we revealed similar morphometric/allometric rules developed via a single astogenic pathway. In regular colonies, this pathway was driven by the presence/absence of intra‐circlet budding polyps, while in chimeras, by the distances between the two founder polyps. In addition, we identified the intra‐circlet budding as the origin of first branching, if BPC distances are kept <1.09 ± 0.25 mm. Conclusions: The emerged allometric/morphometric rules indicate the existence of a positional information paradigm for polyps' landscape distribution, where each polyp creates its own positional field of morphogen gradients through six inductive sites, thus forming six positional fields for the development of the archetypal "six‐polyp crown". Key Findings: polyps landscape, chimera, S. pistillata, allometry, morphometry, coral